issues of Urgent Judiciary in the Iraqi Civil Procedure Law, a Comparative Analytical Study - Ahmed, Atta Abdul Hakim (Journal of Legal and Political Studies, 2015)
The legislature has established beside of the ordinary courts which solves the conflicts between the legal people and entities about their rights and duties after specific legal procedures and adequate investigations, summary judgment which ensures temporary protection in the cases which are worried about it from pass of time, without prejudice to the origin disputed rights.The legislator has been subjected the litigation in the urgent cases to the procedures prescribed for ordinary pleas as long as it suits to its nature. So we tried in this research to determine the procedures that are consistent with the nature of these procedures and those which are not consistent with it, and that’s through two parts. We have allocated the first part to define the summary judgment and determination of the conditions of its jurisdiction. and the second one to analyze the rules of the trial in summary judgment. and in the Conclusion we have showed the conclusions we have reached through the study.
Keywords: legislature; duties; legal procedures; rights